Questionnaire for measuring organisational attributes in dental-care practices: psychometric properties and test-retest reliability - Götz, Katja; Hasse, Philipp Robert; Szecsenyi, Joachim; Campbell, Stephen (International dental journal, 2016)
Background The consideration of organisational aspects, such as shared goals and clear communication, within the health care team is important to ensure good quality care. In primary health care, the instrument Survey of Organizational Attributes for Primary Care (SOAPC) is available to measure organisational attributes of care. However, there is no instrument available for dental care. The aim of the present study was to investigate psychometric properties and test-retest reliability of the version of SOAPC adapted for dental care, namely the Survey of Organizational Attributes in Dental Care (SOADC). Methods The SOADC consists of 21 items in the following four subscales: communication; decision making; stress/chaos; and history of change. Convergent construct validity was measured using the job satisfaction scale. A total of 287 dental-care practices were asked to participate in the validation study. Psychometric properties and test-retest reliability were observed. Results A total of 43 dental-care practices responded to the survey. At baseline, 178 dental-care staff completed the questionnaire, and 4 weeks later 138 did so. Internal consistency, measured by Cronbach's alpha, was 0.718 or higher in the subscales. The test-retest reliability for each subscale and the overall SOADC score demonstrated good correlations over the 4-week test-retest interval, except for ‘history of change’. A strong correlation with the aggregated job-satisfaction scale showed high convergent construct validity of SOADC. Conclusions The consideration of organisational aspects from the perspective of dental-care teams is important for providing good quality of care. The SOADC is a reliable instrument with good psychometric properties and is suitable for the evaluation of organisational attributes in dental-care practices.